Targeting the extracellular matrix for delivery of bioactive molecules to sites of arthritis. (22nd November 2018) - Schultz, Christopher
Abstract : Modifications to the extracellular matrix (ECM) can be either causal or consequential of disease processes including arthritis and cancer. In arthritis, the cartilage ECM is adversely affected by the aberrant behaviours of inflammatory cells, synoviocytes and chondrocytes, which secrete a plethora of cytokines and degradative proteases. In cancer, the ECM and stromal cells are linked to disease severity, and metalloproteinases are implicated in metastasis. There have been some successes in the field of targeted therapies, but efficacy depends upon the type and stage of disease. ECM targets are becoming increasingly attractive for drug delivery, owing to changes in ECM structure and composition in the diseased state, and the long in vivo half‐life of its components. This review will highlight various strategies for targeting therapeutics to arthritic joints, including antibody and peptide‐mediated drug delivery platforms to aid delivery to the ECM and retention at disease sites. Linked Articles: This article is part of a themed section on Translating the Matrix. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v176.1/issuetoc